Self-Fluid Management in Prevention of Kidney Stones. Issue 27 (July 2015) - Xu, Chang; Zhang, Chao; Wang, Xiao-Long; Liu, Tong-Zu; Zeng, Xian-Tao; Li, Shen; Duan, Xiao-Wen; Harris., Kevin
<x xml:space="preserve">Abstract</x> Abstract Epidemiologic studies have suggested that daily fluid intake that achieves at least 2.5 L of urine output per day is protective against kidney stones. However, the precise quantitative nature of the association between fluid intake and kidney stone risk, as well as the effect of specific types of fluids on such risk, are not entirely clear. We conducted a systematic review and dose–response meta-analysis to quantitatively assess the association between fluid intake and kidney stone risk. Based on a literature search of the PubMed, Embase, and Cochrane Library databases, 15 relevant studies (10 cohort and 5 case–control studies) were selected for inclusion in the meta-analysis with 9601 cases and 351, 081 total participants. In the dose–response meta-analysis, we found that each 500 mL increase in water intake was associated with a significantly reduced risk of kidney stone formation (relative risk (RR) = 0.93; 95% CI: 0.87, 0.98; P < 0.01). Protective associations were also found for an increasing intake of tea (RR = 0.96; 95% CI: 0.93, 0.99; P = 0.02) and alcohol (RR = 0.80, 95% CI: 0.75, 0.85; P < 0.01). A borderline reverse association were observed on coffee intake and risk of kidney stone (RR = 0.88; 95% CI: 0.76, 1.00; P = 0.05). The risk of kidney stones was not significantly related to intake of juice (RR = 1.02, 95% CI: 0.95, 1.10; P = 0.64), soda (RR = 1.03; 95% CI: 0.90, 1.17; P = 0.65), or milk (RR = 0.96; 95% CI: 0.88, 1.03; P = 0.21). Subgroup analysis and sensitivity analyses showed inconsistent results on coffee, alcohol, and milk intake. Increased water intake is associated with a reduced risk of kidney stones; increased consumption of tea and alcohol may reduce kidney stone risk. An average daily water intake was recommended for kidney stone prevention.